Modelos de governança corporativa e sociedades de economia mista: qual o modelo de governança mais adequado às sociedades de economia mista? - Andre de Albuquerque Sgarbi (2011)
The mixed companies (jointly owned by the state and private citizens or companies) are today an effective instrument for obtaining private resources, which can be invested in activities that simultaneously generates financial return for the private investors and fulfill a determined public interest. The private shareholders invests in a mixed companies looking for the financial return, while the state-shareholder, who necessarily controls the company, creates it and place public resources in order to fulfill a social demand. However, the coexistence of shareholders whit antagonistic interests does not occur without conflict. It is common that decisions taken by the state-shareholder impact relevantly the companys profits, and, as a consequence, the return of the investments made by the private shareholders. Thus, the mixed companies demand a specific corporate governance model, that suits its peculiarities. This model should accommodate the interest of the public and state shareholders. The goal of this work is, in first place, to review some institutes related to the corporate governance of private companies, presenting the model that we understand is more suitable for these companies. Next, we propose an adaption of this model for the mixed companies.